Recommendations for agriculture programs on how to measure impacts on diets and nutrition - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
This brief, along with a series of A4NH strategic briefs, were shared widely to inform the One CGIAR process. Authored by A4NH researchers from IFPRI it was made available online. Less than a year after publication, it is in the top 25% of all research outputs scored by Altmetric.